Development of Wireless Central Monitor Using X-bee Pro S2C (Electrocardiogram and Heart Rate) - Ulumiddiniyah, Bariroh Izzatul; Irianto, Bambang Guruh; Hamzah, Thorib (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2020)
Centralized monitoring of the condition of patients with serious conditions that are carried out continuously and in real-time is very important. in the development of previous researchers have some shortcomings, namely sending data still using cable, completeness of parameters that are still small, close delivery distance, not real-time, and continue. The purpose of this study is that the thick system is done wirelessly, more parameters, longer delivery distance, and can monitor electrocardiogram and heart rate in real-time and continue. the contribution of this research is that the wireless system can send ECG and bpm in real-time, long-distance, and continuously. To make deliveries in real-time, this study uses 2 transmitters and 2 receivers. Electrocardiogram signal obtained from tapping Lead II, then processed using a microcontroller circuit and the results in the form of a heart signal will be. Data is sent using X-Bee Pro. Data is displayed in the form of a patient's heart and BPM signals. In measuring BPM values ​​obtained error values ​​in module 1 0.1388% for BPM 240 and 0.093% for BPM 180, in module 2 0.1388% for BPM 240 and 0.185% for BPM 180, data transmission can be done well at a distance of 8 meters, 10 meters, and 25 meters with a barrier. The results of this study indicate that sending wirelessly can be done at a certain distance and in real-time. This research can be implemented in a central monitor in a hospital with more patients